Back Cover: Nanographenes: Ultrastable, Switchable, and Bright Probes for Super‐Resolution Microscopy (Angew. Chem. Int. Ed. 1/2020). Issue 1 (6th December 2019) - Liu, Xiaomin; Chen, Shih‐Ya; Chen, Qiang; Yao, Xuelin; Gelléri, Márton; Ritz, Sandra; Kumar, Sachin; Cremer, Christoph; Landfester, Katharina; Müllen, Klaus; Parekh, Sapun H.; Narita, Akimitsu; et al.
Abstract : Super‐resolution fluorescence microscopy has enabled important breakthroughs in biology and materials science. In their Research Article on page 496, X. Liu, M. Bonn, and co‐workers introduce nanographenes as a new class of fluorophores for super‐resolution fluorescence microscopy. Nanographenes exhibit outstanding photophysical properties, such as high brightness, intrinsic blinking even in air, excellent fluorescence recovery, and stability over several months.